2016
DOI: 10.1186/s40550-016-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates in soft PVC products used in food production equipment and in other food contact materials on the Danish and the Nordic Market 2013-2014

Abstract: Background: Food contact materials (FCM) containing phthalates can be a source of food contamination when used in plastics for food production equipment, in utensils for food contact and in packaging. Since 2008 several of the phthalates used for FCM were regulated in the EU; some of them because they were well-known endocrine disruptors. Results of the Danish Food Authorities control in 2008 and 2009 showed 23 % non-compliant samples. Critical FCMs turned out to be those made from plasticised PVC and sold as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The detection procedure was according to the method described in the literature (DEHA[27], DEHP[28]). The FCM plastic was rinsed with HPLC-grade water and crushed into pieces.…”
Section: Methodsmentioning
confidence: 99%
“…The detection procedure was according to the method described in the literature (DEHA[27], DEHP[28]). The FCM plastic was rinsed with HPLC-grade water and crushed into pieces.…”
Section: Methodsmentioning
confidence: 99%
“…Polyvinyl chloride (PVC) has seen extensive use in food-contact applications including conveyor belts, rollers, piping, tubing, gaskets, gloves, countertops, and packaging. PVC conveyors have been the topic of extensive study. The viability of pathogenic microorganisms on and transfer of such organisms to and from PVC conveyor belts have been studied extensively. Some research has suggested that PVC conveyor belts may be more difficult to effectively clean and sanitize than other food-contact surfaces such as stainless-steel .…”
Section: Introductionmentioning
confidence: 99%
“…Their uses broaden over time to meet the growing industrial demand to the extent that plasticizers are an ubiquitous part of contemporary lifestyle. They have been reported in a wide range of commercial products, such as food packaging, toys, medical devices and protective gloves [ 3 , 4 , 5 , 6 ]. Although plasticizer consumption is tremendous, their use is not without risks.…”
Section: Introductionmentioning
confidence: 99%